If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(y+2)/2-(2y-6)/3=1
We simplify the equation to the form, which is simple to understand
(y+2)/2-(2y-6)/3=1
Reorder the terms in parentheses
( + 0.5y+1)-(2y-6)/3=1
Remove unnecessary parentheses
+ 0.5y+1-(2y-6)/3=1
Reorder the terms in parentheses
+ 0.5y+1-( + 0.666666666667y-2)=1
Remove unnecessary parentheses
+ 0.5y+1-0.666666666667y+2=1
We move all terms containing y to the left and all other terms to the right.
+ 0.5y-0.666666666667y=+1-1-2
We simplify left and right side of the equation.
-0.166666666667y=-2
We divide both sides of the equation by -0.166666666667 to get y.
y=12
| 47-4m=7-12m | | 38.2x+41.7-12.9x-43.3= | | 77=4-10y+3 | | 8+x=14-2x | | -60x^2+5=0 | | -7w-3w+4w=-15 | | -19+7=12 | | -12(a-12)=-50 | | 8g+20=76 | | 8+x=12-2x | | 7(1+7m)=7+6m | | 21-3(2-a)=-12 | | 8+x=13-2x | | 15x-30(x+4)=9(x-25) | | 1.9+6p=7.69 | | -7(1+4N)-3N=-224 | | 3n+4=5n-20 | | 6(3-4.5x)=8.5-9x | | .666x=6 | | x^3+4x=101 | | 9x+14=-6(12+x)+38 | | 7/22= | | x(x+3)(x-2)=0 | | y+2/4-y-3/3=1/2 | | 5.6x-7.3=9.2+8.7x | | 3(x+7)-14x+13= | | 14x-6=42 | | 3h+10=-2 | | 8q+p-9p-p= | | 5b^2+27b+28=0 | | 2.50m+4m=26 | | -3c-12-c=-8 |